2012
DOI: 10.1111/j.1365-2966.2012.21283.x
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent simulations of emission from the FSRQ PKS 1510−089: multiwavelength variability of external Compton and synchrotron self-Compton models

Abstract: We present results of modelling the broad‐band spectral energy distribution (SED) and multiwavelength variability of the bright flat spectrum radio quasars PKS 1510−089 with our time‐dependent multizone Monte Carlo/Fokker–Planck code. As the primary source of seed photons for inverse Compton scattering, we consider radiation from the broad‐line region (BLR), from the hot dust of the molecular torus and the local synchrotron radiation [synchrotron self‐Compton (SSC)]. We evaluate the viability of different Comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 56 publications
0
48
0
1
Order By: Relevance
“…It was suggested that the inverse Compton (IC) emission in FSRQ was produced through the synchrotron self-Compton (SSC) mechanism or from external seed photons from the BLRs. These photons would be up-scattered by the synchrotron electrons (e.g., Chen et al 2012). The longstanding unified scheme for radio-loud AGN proposes that the Fanaroff-Riley I and II radio galaxies (Fanaroff & Riley 1974) are the underlying progenitors of BL Lacs and FSRQs galaxies (Bicknell 1995;Fossati et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the inverse Compton (IC) emission in FSRQ was produced through the synchrotron self-Compton (SSC) mechanism or from external seed photons from the BLRs. These photons would be up-scattered by the synchrotron electrons (e.g., Chen et al 2012). The longstanding unified scheme for radio-loud AGN proposes that the Fanaroff-Riley I and II radio galaxies (Fanaroff & Riley 1974) are the underlying progenitors of BL Lacs and FSRQs galaxies (Bicknell 1995;Fossati et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…( Abdo et al 2009a( Abdo et al , 2010bAcero et al 2015;Ackermann et al 2011aAckermann et al ,b, 2015Aller et al 2011;Bai, et al 1998;Bastieri et al 2011;Chen et al, 2012;Fan & Xie 1996;Fan et al 2011;Ghisellini et al 2010;Gu 2014;Gu & Li 2013;Gupta 2011;Gupta et al 2012;Hu, et al 2006;Marscher et al 2011;Nolan et al 2012;Romero et al 2002;Urry 2011;Wills et al 1992;Wu, et al 2007;Yang et al 2010aYang et al ,b, 2012aYang et al ,b, 2014You & Cao, 2014). Quite recently, Massaro et al (2015) published the largest blazar sample (The 5th edition of the Roma-BZCAT, see the BZCAT 5.0 (http://www.asdc.asi.it/bzcat/).…”
Section: Introductionmentioning
confidence: 99%
“…4.1), we find γγ-pair production being negligible for the parameter set used for the above model fits and below the last LAT data point (Barnacka 2013). Chen et al (2012) modelled the last flare in the extended early 2009 flaring episode of this source by using a time-dependent Monte Carlo Fokker-Planck code, where the emission region is treated as an extended cylindrical volume within the jet. In addition to a particle "pick-up" term in the Fokker-Planck equation, they also included a stochastic acceleration term and took into account all external and internal target photon fields.…”
Section: Modeling the Pks 1510-089 Multifrequency Sedmentioning
confidence: 99%